A hybrid network security algorithm based on Diffie Hellman and Text-to-Image Encryption algorithm. (2nd January 2019) - Abusukhon, Ahmad; Anwar, Muhammad Naveed; Mohammad, Zeyad; Alghannam, Bareeq
Abstract: Nowadays, the rapid growth of Internet applications open the doors for people to communicate and do business around the world and thus saving time, efforts and money. However, the success of these applications is based on protecting the data from hackers. It is well known that preventing sensitive data from hackers while they are sent through the global network is a big challenge. There are many techniques used for securing data. Some of these techniques are based on encrypting a readable text into an unreadable text using mathematical operations, while other techniques are based on encrypting a readable text into an image (e.g., the Text-to-Image Encryption algorithm – TTIE) or into musical notes using an encryption key. The encryption key must be secure and should not be sent through the Internet. This paper proposes adding a new security level to the TTIE algorithm, and demonstrates how the encryption key produced by the TTIE algorithm is exchanged with the other party using the Diffie Hellman technique. Thus, this paper proposes a modified TTIE algorithm called the Diffie Hellman Text-to-Image Encryption algorithm (DHTTIE), and tests and analyses the proposed algorithm.